2020
DOI: 10.1093/ejcts/ezaa287
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcomes of thoracic surgery patients during the COVID-19 pandemic

Abstract: OBJECTIVES The goal of this study was to describe the clinical features and outcomes of thoracic surgery patients during the coronavirus disease 2019 (COVID-19) pandemic. METHODS Thirty-five patients were treated at the 12 de Octubre University Hospital in Madrid between 1 March 2020 and 24 April 2020 during the COVID-19 pandemic. Patient demographics, surgical procedures, complications, COVID-19 symptoms and outcomes were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…These guidelines, together with the use of COVID-19-free areas of the hospital, were particularly important in Spain, in which the high incidence of SARS-CoV-2 and consequent hospital overload had a major impact on surgical procedures. Importantly, this strategy allowed for the surgical treatment of selected patients with little to no excess morbidity and mortality [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…These guidelines, together with the use of COVID-19-free areas of the hospital, were particularly important in Spain, in which the high incidence of SARS-CoV-2 and consequent hospital overload had a major impact on surgical procedures. Importantly, this strategy allowed for the surgical treatment of selected patients with little to no excess morbidity and mortality [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Similar approaches to prioritize patients undergoing cardiac surgery and their preoperative screening for COVID-19 have also been recommended, Keskin et al, developed a different screening system to decide when to postpone or proceed with elective cardiac or vascular interventions based on a checklist containing relevant symptoms and signs of the disease, history of traveling or patient contact to determine the risk of COVID-19 transmission. [11][12][13] Our study showed that elective cardiovascular surgery procedures could be performed with acceptable mortality rates. Although our mortality rate was 9% during the study period, this result must be interpreted with caution because none of those patients had an elective procedure, in addition, their euroscores were relatively high, two patients who underwent urgent CABG had poor left ventricular function and died with low cardiac output syndrome, the patient who underwent open repair of ruptured AAA died due to acute renal failure, the patient with TVR died also due to renal failure and severe thrombocytopenia which leads to cerebral and massive gastrointestinal system hemorrhage, the remaining two patients died intraoperatively, one had fragile aorta which ruptured after the cross-clamp was removed, the other one was the patient with post-MI VSD, the last two patients who also underwent urgent CABG procedure, died due to postoperative COVID-19 infection.…”
Section: Discussionmentioning
confidence: 63%
“…Adequate use of personal protective equipment (PPE) during aerosol-generating procedures (AGPs), such as endotracheal intubation and airway surgical or endoscopic procedures, and a COVID-19 specifc intraoperative management are paramount in order to prevent cross infections [16]. Although guidelines have been published for the management of surgical patients during the SARS-CoV-2 pandemic, so far, few studies of surgical patients have been reported, and little is known about preoperative routine screening for SARS-CoV-2 infection among surgical patients [4,17].…”
Section: Discussionmentioning
confidence: 99%